Liraglutide Increases Serum Levels of MicroRNA-27b, -130a and -210 in Patients with Type 2 Diabetes Mellitus: A Novel Epigenetic Effect - Giglio, Rosaria Vincenza; Nikolic, Dragana; Volti, Giovanni Li; Stoian, Anca Pantea; Banerjee, Yajnavalka; Magan-Fernandez, Antonio; Castellino, Giuseppa; Patti, Angelo Maria; Chianetta, Roberta; Castracani, Carlo Castruccio; Montalto, Giuseppe; Rizvi, Ali A.; et al. (Metabolites, 2020)
Liraglutide has shown favourable effects on several cardiometabolic risk factors, beyond glucose control. MicroRNAs (miRNAs) regulate gene expression, resulting in post-transcriptional modifications of cell response and function. Specific miRNAs, including miRNA-27b, miRNA-130a, and miRNA-210, play a role in cardiometabolic disease. We aimed to determine the effect of liraglutide on the serum levels of miRNA-27b, miRNA-130a and miRNA-210. Twenty-five subjects with type-2 diabetes mellitus (T2DM), naïve to incretin-based therapy, were treated with liraglutide (1.2 mg/day as an add-on to metformin) for 4 months. miRNAs were quantified using real-time polymerase chain reaction. After liraglutide treatment, we found significant reductions in fasting glucose (from 9.8 ± 5.3 to 6.7 ± 1.6 mmol/L, p = 0.0042), glycosylated haemoglobin (HbA1c) (from 8.1 ± 0.8 to 6.6 ± 1.0%, p = 0.0008), total cholesterol (from 5.0 ± 1.0 to 4.0 ± 0.7 mmol/L, p = 0.0011), triglycerides (from 1.9 ± 1.0 to 1.5 ± 0.8 mmol/L, p = 0.0104) and low-density lipoprotein cholesterol (from 2.9 ± 1.2 to 2.2 ± 0.6 mmol/L, p = 0.0125), while the serum levels of miRNA-27b, miRNA-130a and miRNA-210a were significantly increased (median (interquartile range, IQR) changes: 1.73 (7.12) (p = 0.0401), 1.91 (3.64) (p = 0.0401) and 2.09 (11.0) (p = 0.0486), respectively). Since the changes in miRNAs were independent of changes in all the metabolic parameters investigated, liraglutide seems to exert a direct epigenetic effect in T2DM patients, regulating microRNAs involved in the maintenance of endothelial cell homeostasis. These changes might be implicated in liraglutide’s benefits and may represent useful targets for cardiometabolic management.